Proceeding Anual International Conference on Islamic Studies (AICIS) XIII: Mataram, 18-21 November 2013 - Proceeding... (Direktorat Pendidikan Tinggi Islam Dirjen Pendidikan Islam Kemenag RI, 2013)
st,2/ws.jl.1-2.c.1